Muslims Resistance to Health Protocols in COVID-19 Funeral: A Study of Islamic Law - Zainuddin, Zainuddin; Qudsy, Saifuddin Zuhri; Cahyani, Novita; Zulkifli, Zulkifli; Warman, Arifki Budia (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
Some Muslims have stood up against health protocols for burying COVID-19 corpses. This research aimed to investigate the initial occurrence of this resistance in society, the contributing factors to the resistance, and the implications of the resistance. To date, most studies on resistance focused on social perspectives, but this research probed into the discourse of resistance during COVID-19 from the perspective of legal transformation, especially in Islamic law or fiqh. This study employed a qualitative approach supported by data obtained from printed and electronic media, and informants. The analysis revealed that public resistance to the burial which complied to health protocols was not only embodied in rhetorics or values but made apparent in their attitude. This study concludes that public resistance sucessfully reformed the law by bringing about the new fiqh regarding the burial practice. Since the community might not readily understand and accept this neq fiqh, we advised the government and related institutions to take intensive approaches to introduce this transformation to public.